A Contextual Analysis of High-Fidelity and Low-Fidelity Sessions in Emotion-Focused Couples Therapy. Issue 1 (2nd January 2016) - Novak, Joshua R.; Sandberg, Jonathan G.; Stucki, Bradford; Young, Stephanie; Brown, Andrew; Schade, Lori; Holt-Lunstad, Julianne
Abstract : The purpose of this study was to explore and compare high-fidelity and low-fidelity Emotionally Focused Couples Therapy sessions across the course of treatment. Data were taken from sessions 3, 7, and 11 from two different couples. Grounded theory was used to identify emerging themes from the data. Further, a word frequency query was performed to understand the differences in language use. Results indicated that more primary emotion words were used in high-fidelity than low-fidelity sessions, while more cognitive words were used in the low-fidelity sessions. Different themes were found when comparing the high- and low-fidelity sessions and include primary focus and identifying the couples' cycle. Additional results and clinical implications are discussed.